Integration of robotics in underground mining construction works - Crespo, C.; Rodríguez, F. (Expanding Underground - Knowledge and Passion to Make a Positive Impact on the World, 2023)
Since November 2021, Acciona has been testing the SPOT quadruped robot (Boston Dynamics' Spot) in the underground mining site in Chile, with the main goal of reducing risks for human personnel while increasing process control and productivity. The following tasks are currently being performed by the robot: high precision scanning for section control, high precision scanning after applying shotcrete to perform quality control by measuring the thickness, thermal monitoring of the shotcrete to estimate setting level and early mechanical resistance, image acquisition of the tunnel face that allows generating a geologic report and robotic exploration of the tunnel after blasting, to identify misfired explosives. Acciona's Robotics & Automation team has implemented several sensors over the robotic platform Spot: Leica's RTC360 scanner, Leica's BLK360 scanner and Teledyna's GXM320 thermal camera. Thanks to this integration, the robot can execute scans and taking thermal images. Together with the environment sensing, obstacle detection and autonomous capabilities of the robot, Spot can navigate autonomously through the mine, collecting data and generating automatic reports. The Robot has demonstrated the ability to move through the aggressive environment of a mine with unstable rocks, water and mud, without many problems. Areas with low illumination have been no issue thanks to the LiDAR system incorporated on the robot. Also, the navigation and autonomy systems have been able to work in these circumstances, performing well despite the differences in the environment for each location. This paper covers the design of the activities to be performed by the autonomous system, the system and the integration of its payloads and the results of the integration of this platform into a mining construction site. Since November 2021, Acciona has been testing the SPOT quadruped robot in the underground mining site in Chile, with the main goal of reducing risks for human personnel while increasing process control and productivity. The mining activity is one of the oldest activities that have been in continuous growth since the beginning of it. This is due to the intrinsic need of metals for everyone and the fact that mining is the only way to get minerals such as copper of iron, so much needed in everyone's life. Mining in general and underground mining in particular is an inherently dangerous activity, including fatal risks like fire, explosives, rockslide or heavy machinery moving tons of material in confined spaces. The relation between temperature and mechanical resistance has been attained by performing thermal measurements, penetrometer measurements and high resistance measurements in 109 different shotcrete testing panels obtained at the moment of the shotcrete application.